Formation and Maintenance of the Natural Bypass Vessels of the Brain - Perovic, Tijana; Harms, Christoph; Gerhardt, Holger (Frontiers in Cardiovascular Medicine, 2022)
Ischemic diseases are the leading cause of death and among the leading causes of disability worldwide. The main compensatory mechanism by which our body responds to reduced or blocked blood flow caused by ischemia is mediated by collateral vessels. Collaterals are present in many healthy tissues (including brain and heart) and serve as natural bypass vessels, by bridging adjacent arterial trees. This review focuses on: the definition and significance of pial collateral vessels, the described mechanism of pial collateral formation, an overview of molecular players and pathways involved in pial collateral biology and emerging concepts in preventive conditioning of pial collaterals. Despite their high clinical relevance and recent scientific efforts towards understanding collaterals, much of fundamental collateral biology remains obscure.